Importance of agroecological fairs for the contribution of alternative production systems and their impact on promoting healthy and sustainable eating (Research, Society and Development, 2024)
Agroecology is strengthened in response to the crises generated by current conventional production, bringing socio-environmental discussions. Therefore, family farming is guided by these issues, encouraging short production chains that sell organic products committed to sustainability. The work aims to characterize and show the importance of organic fairs as ways of consolidating a more sustainable agri-food system, as well as the relationship between agroecology and nutrition science, aiming to reframe and expand the concept of healthy eating. To this end, producers and consumers were interviewed at the UFPA Family Agriculture Fair and at the Praça Brasil Organic Products Fair in Belém-PA and the answers were related to other studies. It was observed that the relationship with agroecological production occurred mainly through family influence. The majority reported using agroecological inputs or biofertilizers, of their own production. Fairs were found to be the main places for producers to sell and consumers to purchase.Among the benefits cited from this production, producers highlighted economic improvements and improvements in the quality of the product offered, while consumers claimed health benefits and tastier food. Vegetables stood out as the most purchased products. Finally, it is observed that short production chains prioritize sales of products without pesticides and, the majority, free from activities harmful to biodiversity, being safe for producers, consumers and the environment. Thus, even with little visibility, organic fairs play a huge role in promoting healthy eating.